Disorders of phosphate metabolism. Issue 11 (29th August 2019) - Leung, Jenny; Crook, Martin
Abstract : Phosphate in both inorganic and organic form is essential for several functions in the body. Plasma phosphate level is maintained by a complex interaction between intestinal absorption, renal tubular reabsorption, and the transcellular movement of phosphate between intracellular fluid and bone storage pools. This homeostasis is regulated by several hormones, principally the parathyroid hormone, 1, 25-dihydroxyvitamin D and fibroblast growth factor 23. Abnormalities in phosphate regulation can lead to serious and fatal complications. In this review phosphate homeostasis and the aetiology, pathophysiology, clinical features, investigation and management of hypophosphataemia and hyperphosphataemia will be discussed.